DETERMINING THE COMPETITIVENESS OF ECONOMIC SECTORS USING AN INDEX METHOD BASED ON PRINCIPAL COMPONENT ANALYSIS - Byambajav, Enkh-Amgalan; Artskhuu, Uranchimeg (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
This study constructs a composite competitiveness index for 19 economic sectors in Mongolia over 2015–2024 by applying Principal Component Analysis (PCA) to sectoral indicators including sector GDP, inflow FDI, employment, and average wages. Empirical results show the mining sector attains the highest index scores driven by substantial FDI inflows, higher wages, and employment expansion, whereas the agricultural sector records declining index values associated with a reduced sector GDP and limited investment attraction. By ranking sectors according to the composite index, the analysis provides actionable insights for policymakers and investors: prioritizing diversification of investment sources, targeting human capital and productivity improvements, and designing sectoral development strategies to address structural imbalances. The index also functions as a monitoring tool to track changes in sectoral competitiveness over time and to evaluate the impact of policy interventions. Overall, the study demonstrates that a PCA‑based composite index offers a practical, data‑driven basis for comparing sectoral competitiveness and informing strategic economic planning in Mongolia.